Nearly Unbiased Estimation in Dynamic Panel Data Models with Exogenous Variables - Martin A. Carree (Tinbergen Institute, 2002)
This paper introduces a new estimator for the fixed effects dynamic panel data model withexogenous variables. This estimator does not share some of the drawbacks of recently developed IVand GMM estimators and has a good performance even in small samples. The nearly unbiased estimatoris derived as a bias correction of the within estimator (least squares dummy variable estimator).The estimator is applied to a model of unemployment dynamics at the U.S. state level for the1991-2000 period.
Keywords: C23; 330; panel data; fixed effects; nearly unbiased estimation; Panelforschung; Dynamisches Modell; Bias; Theorie